2019
DOI: 10.1049/iet-pel.2018.5359
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid periodic carrier frequency modulation technique based on modified SVPWM to reduce the PWM noise

Abstract: This study proposed a hybrid periodic carrier frequency modulation (HPCFM) technique based on the modified space vector pulse-width modulation (SVPWM) for two-level three-phase voltage source inverters to eliminate the PWM noise. Owing to PWM technique and switching losses considerations, ear-piercing high-frequency acoustic noise from motor is common. The proposed HPCFM technique is able to remove the high-frequency unpleasant acoustic noise more effectively than conventional PCFM with lower switching losses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Compared to random pulsewidth modulation (PWM) [4, 5], periodic PWM [6, 7], and chaos PWM [8, 9], the programmed PWM [10, 11] utilises the mathematical model of the controlled object to predict the control effect. And by using additional degrees of freedom, it can improve control performance, such as suppressing the inverter losses, output current ripple, motor noise, and torque pulsation.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to random pulsewidth modulation (PWM) [4, 5], periodic PWM [6, 7], and chaos PWM [8, 9], the programmed PWM [10, 11] utilises the mathematical model of the controlled object to predict the control effect. And by using additional degrees of freedom, it can improve control performance, such as suppressing the inverter losses, output current ripple, motor noise, and torque pulsation.…”
Section: Introductionmentioning
confidence: 99%
“…(3). Regarding the optimization of the sideband acoustic noise for improving the acoustics characters, although the sideband noise can be reduced by increasing the carrier frequency above 20 kHz, the noise cannot be eliminated and experiences some negative effects during operation [11]. Generally, it can be confirmed that the sideband harmonic components are related to the frequency modulation (FM) that is affected by the rotating speed of the motor [7,12].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, random bit number generations need higher circuit cost and implementation burden. Hence, the researchers recommended a linear feedback shift register (LFSR) for getting more randomness [35][36][37][38][39]. LFSR is commonly referred to as a pseudo-PWM code generator and works using a digital logical process of a binary number [29].…”
Section: Introductionmentioning
confidence: 99%